Association Between Plasma Concentration of Klotho Protein, Osteocalcin, Leptin, Adiponectin, and Bone Mineral Density in Patients with Chronic Kidney Disease - Marchelek-Mysliwiec, Małgorzata; Wisniewska, Magda; Nowosiad-Magda, Monika; Safranow, Krzysztof; Kwiatkowska, Ewa; Banach, Bolesław; Dołegowska, Barbara; Dołegowska, Katarzyna; Stepniewska, Joanna; Domanski, Leszek; Pawlik, Andrzej; Ciechanowski, Kazimierz (Hormone and Metabolic Research, 2018)
Patients with early-stage chronic kidney disease (CKD) are susceptible to changes in metabolic processes. Partial loss of kidney function leads to homoeostatic disturbances in bone and fatty tissue. The aim of this study was to investigate the association between plasma concentrations of Klotho protein, FGF23, leptin, adiponectin, osteocalcin, and bone mineral density (BMD) in patients with CKD in the pre-dialysis period. The study involved 52 patients with CKD and 23 patients with no kidney disease. In both groups, BMD, body mass index and serum or plasma concentrations of lipids, glucose, creatinine, calcium, phosphorus, parathormone, leptin, adiponectin, osteocalcin, Klotho, and FGF23 were measured. The group with CKD had statistically significant higher concentrations of leptin (p<0.001), parathormone (p<0.001), and osteocalcin (p<0.001) in comparison with the control group. Patients with CKD also had statistically significant lower BMD in the femoral neck in comparison with the control group. Osteocalcin correlated negatively with BMD. The results of our study suggest that elevated osteocalcin is the most sensitive marker of decreased bone mass in patients with CKD. Osteocalcin correlated negatively with BMD and GFR. The loss of bone mass in CKD patients was greatest in the femoral neck.
Keywords: Klotho protein; osteocalcin; leptin; adiponectin; bone mineral density; chronic kidney disease